How Undergraduate Science Students Use Learning Objectives to Study - Bethany Osueke (American Society for Microbiology, 2018)
Learning objectives communicate the knowledge and skills that instructors intend for students to acquire in a course. Student performance can be enhanced when learning objectives align with instruction and assessment. We understand how instructors should use learning objectives, but we know less about how students should use them. We investigated students’ use and perceptions of learning objectives in an undergraduate science course at a public research university. In this exploratory study, students (n = 185) completed two open-ended assignments regarding learning objectives and we analyzed the content of their answers. We found that students used learning objectives in ways that reflected the recommendations of past and present instructors, suggesting that students are receptive to instruction on how to use learning objectives. Students generally found learning objectives to be useful because the objectives helped them to narrow their focus and organize their studying, suggesting that students may need additional help from instructors in order to self-direct their learning. Students who chose not to use learning objectives often found other resources, such as case studies covered in class, to be more helpful for their learning. Some of these students recognized that the concepts included in case studies and learning objectives overlapped, pointing to a benefit of alignment between instructional activities and learning objectives. These qualitative results provide the data necessary for designing a quantitative instrument to test the extent to which students’ use of learning objectives affects their performance.